Analysis of Barriers to Elementary School Students’ Critical Thinking Skills in Science Subjects - Muhammad Alditia, Lalu; Fadillah, Nurul; Hanis, Muhsin (LPPM STKIP Kusuma Negara, 2024)
Science education in elementary school serves to equip students with fundamental scientific knowledge and skills. However, learning that is done often only emphasizes memorizing concepts without developing critical thinking skills. This study identifies the constraints in developing elementary students' critical thinking skills in science subjects through a systematic literature review using the PRISMA protocol to collect relevant data and information. The analysis revealed two main factors that become obstacles, namely internal student factors and teacher quality factors. Internal student factors include low motivation and active participation, low self-confidence, lack of learning independence, and students' unfamiliarity with learning that requires critical thinking skills. Meanwhile, teacher quality factors include the application of inappropriate learning strategies and models, teacher-centered learning, lack of development of supporting learning tools and media, lack of teacher knowledge about critical thinking competencies, and the use of evaluation methods that have not maximally explored students' critical thinking skills. These findings provide new insights into the inhibiting factors that need to be overcome so that science learning in elementary schools can optimize the development of student's critical thinking skills as one of the important 21st-century competencies.